Investigation of the Mechanisms Underlying the Development and Evolution of the Cerebral Cortex Using Gyrencephalic Ferrets - Shinmyo, Yohei; Hamabe-Horiike, Toshihide; Saito, Kengo; Kawasaki, Hiroshi (Frontiers in Cell and Developmental Biology, 2022)
The mammalian cerebral cortex has changed significantly during evolution. As a result of the increase in the number of neurons and glial cells in the cerebral cortex, its size has markedly expanded. Moreover, folds, called gyri and sulci, appeared on its surface, and its neuronal circuits have become much more complicated. Although these changes during evolution are considered to have been crucial for the acquisition of higher brain functions, the mechanisms underlying the development and evolution of the cerebral cortex of mammals are still unclear. This is, at least partially, because it is difficult to investigate these mechanisms using mice only. Therefore, genetic manipulation techniques for the cerebral cortex of gyrencephalic carnivore ferrets were developed recently. Furthermore, gene knockout was achieved in the ferret cerebral cortex using the CRISPR/Cas9 system. These techniques enabled molecular investigations using the ferret cerebral cortex. In this review, we will summarize recent findings regarding the mechanisms underlying the development and evolution of the mammalian cerebral cortex, mainly focusing on research using ferrets.